The Influence of Using Animaker Media in Improve to Teach Recount Text - Muhammad Sofyan Al Aziz; Dias Andris Susanto; Dyah Nugrahani (Melati Institute, 2023)
This research was motivated by the fact that there were still many students who experience difficulties in writing and understanding recount text and teachers who apply monotonous or less varied learning methods. The formulation of the problem of this research was whether there was an effect of using Animaker in improving the ability to write recount text in students’ class at XII SMA N 1 Comal? In connection with this, the aim of this research is to find out whether there was an influence of Animaker on the learning outcomes of recount text in class XII SMA N 1 Comal. This study used a quantitative approach. This research used an experimental design consisting of two groups, namely the experimental group and the control group. The population in this study was class XII students of SMA N 1 Comal for the 2023/2024 academic year. The samples from this research were class XII MIPA 1 totaling 36 students and class XII IPA 6 totaling 36 students. This technique in the research was random sampling. Based on the data research results, shows that used Animaker media in writing recount text could improve the ability to write recount text and convey past experiences in written form. Based on data analysis, the Pre-test result in the experimental group was 62.22 while the Post-test was 80.08. In the control group, the Pre-test result was 60.61 while the Post-test result was 70.47. Apart from that, based on the paired sample test table, the result shows a sig (2 tailed) of 0.000 < 0.05. Therefore, it can be concluded that there was a difference in the average learning outcomes of students in the Pre-test experimental class and Post-test experimental class used Animaker.